Bile acid pathways in Caprinae gut microbiota: adaptive shifts in microbial metabolism and community structure - Shang, Kai-Meng; Liu, Rui; Ni, Hong-Bo; Ma, He; Su, Jin-Wen; Yu, Hai-Long; Guo, Li; Chen, Bei-Ni; Zhang, Xiao-Xuan; Yang, Xing (Frontiers in Microbiology, 2025)
IntroductionThe gut microbiota plays a central role in host metabolism and immunity, in part through bile acid (BA) biotransformation. In Caprinae animals such as goats and sheep, this process is critical for nutrient absorption, immune regulation, and intestinal homeostasis, yet the microbial taxa and functional pathways involved remain poorly characterized.MethodsBy leveraging 7,530 high-quality non-redundant metagenome-assembled genomes (MAGs) from Caprinae gut microbiomes, this study systematically characterized microbial diversity, taxonomic composition, and bile acid (BA)-related metabolic pathways through genome annotation, phylogenetic inference, and statistical analyses.ResultThe results revealed a diverse gut microbiota across 28 phyla, with Bacillota_A being the most dominant. A significant number of genes (8,290) from 5,217 genomes were identified to be involved in BA transformation pathways, including deconjugation, oxidation, and dehydroxylation. Bacteria from the Bacillota_A phylum were the primary carriers of BA-related genes. Among the MAGs, 1,845 encoded bile salt hydrolase (BSH), an enzyme crucial for the initial step of BA metabolism. Comparative analysis with human and pig gut microbiota highlighted a distinct BA metabolic profile in Caprinae animals, characterized by a higher proportion of BSH-related genes. Functional profiling of BSH-carrying MAGs within the genus Alistipes revealed significant differences in carbohydrate-active enzymes (CAZymes), indicating distinct metabolic repertoires that may reflect divergent ecological roles in the intestinal environment. Microbial taxonomic composition and bile acid (BA)-metabolizing potential varied markedly across the ten intestinal segments of Ovis aries, with the colon, cecum, and rectum showing the highest microbial diversity and functional gene abundance. Key BA-transforming enzymes (BSH, 7α-HSDH, and baiB) were widely distributed, with particularly high abundances in the jejunum and ileum, indicating region-specific specialization in BA metabolism.DiscussionThis study provides new insights into the ecological and metabolic functions of gut microbiota in Caprinae animals, emphasizing the unique BA metabolic profiles and the functional potential of BSH-carrying MAGs, which have broader implications for understanding host-microbiota interactions in health and disease.